2015
DOI: 10.1681/asn.2014070678
|View full text |Cite
|
Sign up to set email alerts
|

Myocardin-Related Transcription Factor A Epigenetically Regulates Renal Fibrosis in Diabetic Nephropathy

Abstract: Diabetic nephropathy (DN) is one of the most common complications associated with diabetes and characterized by renal microvascular injury along with accelerated synthesis of extracellular matrix proteins causing tubulointerstitial fibrosis. Production of type I collagen, the major component of extracellular matrix, is augmented during renal fibrosis after chronic exposure to hyperglycemia. However, the transcriptional modulator responsible for the epigenetic manipulation leading to induction of type I collage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
78
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 51 publications
6
78
2
Order By: Relevance
“…All these findings suggest that Nox4 protein levels rise under fibrogenic (predominantly diabetic) conditions, and this contributes to the ensuing nephropathy and fibrosis. Consistent with this scenario and our new findings, a recent paper reports that MRTFdeficient mice are largely protected against DKD (16). However, results obtained with whole body Nox4 knock-out mice are controversial or more complex.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…All these findings suggest that Nox4 protein levels rise under fibrogenic (predominantly diabetic) conditions, and this contributes to the ensuing nephropathy and fibrosis. Consistent with this scenario and our new findings, a recent paper reports that MRTFdeficient mice are largely protected against DKD (16). However, results obtained with whole body Nox4 knock-out mice are controversial or more complex.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, cytoskeleton remodeling is not only an early feature of the phenotypic shift but also a key driver of the ensuing transcriptional reprogramming, thereby linking cell structure to gene expression via the MRTF/SRF pathway (14). Accordingly, we and others have shown that genetic or pharmacological inhibition of MRTF prevents myofibroblast transition (8,10) and lessens organ fibrosis (15)(16)(17).…”
mentioning
confidence: 98%
“…Further investigation is warranted to seek a unified model wherein chromatin remodeling and histone modifying proteins cooperate to regulate different pathophysiological events. Finally, our recent findings suggest that MRTF-A regulates cellular fibrogenesis likely through the same set of epigenetic factors as described here [15,16]. Collectively, these data allude to a broad role for MRTF-A in cellular response to injuries signals, which is consistent with a recent paper linking MRTF-A activation to wound healing [43].…”
Section: Discussionsupporting
confidence: 90%
“…The regulation of proangiogenic factor cyr61 upon mechanical overload depends on the cooperation of MRTF-A and p300 (Hanna et al, 2009). A recent study also determined that MRTF-A can recruit p300 to the collagen promoters and activate this target gene transcription, thus contributing to the progression of renal fibrosis and diabetic nephropathy (Xu et al, 2014). Using ChIP assay, we observed a clear increase in the acetylation levels of H3K9 H3K14 and H4 at the SRF binding site of the VE-cadherin promote, when HUVECs were overexpressed with MRTF-A.…”
Section: Discussionmentioning
confidence: 99%